(3GdHGgQ (B((3aj Yde GdQjGVjGJ(B)s - (3CHh GdfUQ GdSehGd Hf jMji Hf YHGS GdeZQHj GdCfOdSj,J (B570 (3g` s
(3ChdgG (B:s
(3bGd GdSehCd(B: (3HYO MeOGddg Ydi Sff BdGFg hgfi fYeGFg hGdUdGI Ydi eMeO NGJe CfHjGFg s
(3BNQgG (B:s
(3agPG eGQCjfG Cf fhOYg gPG GdcJGH ef CUhd GdUfGYI GdYOOjI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B892 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA QjGVjGJ (B- (3bSe (B3 - (3U (B19 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(2718) s
Keywords: (3GdQjGVjGJs